2021
DOI: 10.3389/fphys.2020.571416
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Immunity, and COVID-19: How Age Influences the Host Immune Response to Coronavirus Infections?

Abstract: The novel coronavirus severe acute respiratory syndrome coronavirus 2 causing the Coronavirus disease (COVID-19) pandemic has ravaged the world with over 72 million total cases and over 1.6 million deaths worldwide as of early December 2020. An overwhelming preponderance of cases and deaths is observed within the elderly population, and especially in those with pre-existing conditions and comorbidities. Aging causes numerous biological changes in the immune system, which are linked to age-related illnesses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
344
3
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(376 citation statements)
references
References 186 publications
(521 reference statements)
21
344
3
8
Order By: Relevance
“…Moreover, immunosenescence occurs with aging, so we anticipated age to be a potential effect modifier in the relationship between mAb receipt and study outcomes. 14 Therefore, we planned a priori to select non-infused patients using propensity scores within age strata consistent with the EUA criteria: less than 55 years, 55 years to less than 65 years, and 65 years of age and older. 9 Patients receiving mAb infusion and the selected comparator patients across all age strata were then combined to constitute the study population.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, immunosenescence occurs with aging, so we anticipated age to be a potential effect modifier in the relationship between mAb receipt and study outcomes. 14 Therefore, we planned a priori to select non-infused patients using propensity scores within age strata consistent with the EUA criteria: less than 55 years, 55 years to less than 65 years, and 65 years of age and older. 9 Patients receiving mAb infusion and the selected comparator patients across all age strata were then combined to constitute the study population.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested the significant reduction of immunologically important cells which provide adaptive immunity, such as T-cells in severe cases of COVID-19 [ 205 , 206 ]. Hence, T-cells in, for example, CD4 + and CD8 + cell populations have been found to be significantly declined compared to cells that provide innate immunity, such as macrophages and neutrophils in mild to severe cases of the SARS-CoV-2 infection [ 207 ].…”
Section: Response Rate Of Activated T-cell Types In Covid-19mentioning
confidence: 99%
“…During development, dose optimization of the Moderna vaccine has been performed towards optimal protection of the elderly, exploring doses of 25, 50, 100 and 250ug, as the elderly show reduced immune response on vacccination[ 3 ]. Laboratory-assessed immunity levels typically exceeded those seen in the plasma of reconvalescent patients who have a protection of 83% for at least 5 months[ 4 ].…”
Section: Introductionmentioning
confidence: 99%